Panel depicting Pradyumna image - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel depicts Pradyumna. While Meister identifies the sculpture as Varuna, the God of oceans and the dikpala of the west direction, Packert-Atherton identifies him as Pradyumna, one of the Vrishni cult deities of the Pancharatra sect. Pradyumna is seated in the lalitasana posture on his mount, the mythical sea creature called makara. He holds a bow in his left hand and is surrounded by four female attendants. Two attendants in the foreground are seated on circular seats and two in the background are standing. The seated lady on the left is holding an arrow. The seated lady on the right has long braided hair. The faces, feet, and hands of the figures are broken and their attributes are not clear.